HUBUNGAN LOC DAN MOTIVASI BERPRESTASI DENGAN SELF EFFICACY DAN MINAT BERWIRAUSAHA - Wulan Oktabriyantina; Raden Gunawan Sudarmanto; Pujiati Pujiati (JEE (Jurnal Edukasi Ekobis), 2014)
The purpose of this research is to know the correlations between Locus Of Control (LOC) and achievement motivation with self efficacy and students’ interest in entrepreneurship economics education. The population in this study were students of economic education class of 2010,2011,2012 and 2013 with the total were 357 students while the sample of 148 students were determined using Cochran formula and multistage cluster sampling techniques. The method used was descriptive associative method with an ex post facto approach and survey. The hypothesis was tested using linear regression with path analysis. The results showed that: (1)There is a correlation between locus of control and interest in entrepreneurship; (2)There is a correlation between achievement motivation and interest in entrepreneurship; (3)There is no correlation between achievement motivation and locus of control; (4)There is a correlation between locus of control and self efficacy; (5)There is a correlation between achievement motivation and self efficacy;(6)There is a correlation between self efficacy and interest in entrepreneurship.Penelitian ini bertujuan untuk mengetahui hubungan antara Locus Of Control (LOC) dan motivasi berprestasi dengan self efficacy dan minat berwirausaha mahasiswa Pendidikan Ekonomi. Populasi dalam penelitian ini adalah mahasiswa Pendidikan Ekonomi angkatan 2010,2011,2012 dan 2013 yang berjumlah 357 dengan sampel 148 mahasiswa yang ditentukan menggunakan rumus Cochran dan teknik multistage cluster sampling. Metode yang digunakan adalah metode deskriptif asosiatif dengan pendekatan ex post facto dan survey. Pengujian hipotesis menggunakan uji regresi linear dengan analisis jalur. Hasil penelitian menunjukkan bahwa: (1)Terdapat hubungan antara locus of control dengan minat berwirausaha; (2)Terdapat hubungan antara motivasi berprestasi dengan minat berwirausaha; (3)Tidak terdapat hubungan antara locus of control dengan motivasi berprestasi; (4)Terdapat hubungan antara locus of control dengan self efficacy; (5)Terdapat hubungan antara motivasi berprestasi dengan self efficacy; (6)Terdapat hubungan antara self efficacy dengan minat berwirausaha.Kata kunci : LOC, minat, motivasi, self efficacy